PENERAPAN UU. 23 TAHUN 2004 TENTANG PENGHAPUSAN KDRT DI KOTA DENPASAR - I Nyoman Alit Putrawan (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Domestic violence is a serious problem that must beaddressed with a fair law so that victims who experience physical and mental harm feel protected. Domestic violence can occur based on several reasons and backgrounds. Domestic violence is not allowed. So that the government issues laws and regulations to protect its people from violent injustice. This study aims to analyze the application of Law no. 23 of 2004. Where in its application it will be considered futile if the community does not take part in protecting fellow human beings from violence.